Personality Dynamics and Work Fatigue on Employee Engagement and Its Implications for Turnover Intention (Survey on PT. SBCR) - Maura Mediani Mahadi, Hannum; Kartono, Kartono (Publikasi Indonesia, 2026)
This research is motivated by the increasing dynamics of human resource management which is characterized by high work demands, differences in employee personality characteristics, and the emergence of the phenomenon of work fatigue which has an impact on the level of employee involvement and the tendency of turnover intention. Company data shows fluctuating turnover rates, making it an important concern in employee retention strategies. This study aims to analyze the influence of personality and work fatigue on employee engagement and its implications on turnover intention. The research method used was a quantitative method with a survey approach. The data collection technique was carried out through the distribution of questionnaires to PT SBCR employees with certain sampling techniques. Data analysis uses validity, reliability, classical assumption tests, and hypothesis testing using linear regression. The results of the study showed that personality had a positive and significant effect on employee engagement, work fatigue did not have a significant effect on employee engagement, work fatigue had a positive effect on turnover intention, while employee engagement did not have a significant effect on turnover intention. In addition, employee engagement has not been shown to mediate the relationship between personality and work fatigue on turnover intention. The conclusion of this study shows the importance of managing employee psychological factors as an effort to reduce turnover intention in the organization.